PERAN PEMERINTAH DALAM PENGENTASAN KEMISKINAN DI KABUPATEN TANA TORAJA - S Haruna, Putri Sahni; Mappamiring, Mappamiring; Yusuf, Muh (Universitas Muhammadiyah Makassar, 2024)
This study aims to find out how the role of the Social Service in Poverty Alleviation in Tana Toraja Regency. This research uses a qualitative approach. The number of informants in this study were 6 people. Data collection techniques were carried out using source, method and time triangulation. Selection of informants based on the view of the author that the informant has knowledge, and the informant knows the problem the author is researching. The results of this study indicate that the role of the Social Service in poverty alleviation in Tana Toraja Regency is seen from the aspect of being a Regulator, Dynamist and Facilitator in the Poverty Overcoming Program the government has made great efforts to participate in programs for the poor in Tana Toraja, the government has also participated in data collection to the distribution of social assistance to the Social Service facilitating providing